Revolutionizing English Teaching: A Systematic Literature Review on the Role of Technology in Communicative Language Teaching - Wardoyo, Eko; Herda, Rozanah Katrina; Kozuka, Yoshitaka; Majid, Sheikha (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2025)
English teaching has changed from traditional methods such as memorization to communicative approaches such as Communicative Language Teaching (CLT), where many teachers are now adapting technology to CLT. Over the past decade, numerous studies have been conducted to investigate the application of technology in CLT; however, comprehensive research on this topic remains scarce, particularly when considering the scope of the timeframe. To address this gap, the current study systematically reviews the academic literature published on the application of technology in CLT in articles from 2010 to 2025. This study aims to investigate research trends over the past 15 years and identify key findings from the reviewed studies after applying inclusive and exclusive criteria. A total of 40 articles published and indexed in Scopus were included, and this study follows the PRISMA guidelines and thematic content analysis. The authors identified research trends and discussed key findings. In terms of research trends on this topic, the highest number of articles was published in 2024 (n=5). Then, the country contributing the most to this topic was the United Kingdom (n=6). We also found challenges in the implementation of CLT and discussions on the learning media used and the pedagogical approaches employed for teaching English. Based on this review, it is hoped that it will serve as a reference for future research.